Anti-computing Dissent and the machine - Bassett, Caroline (Manchester University Press, 2022)
We live in a moment of high anxiety around digital transformation. Computers are blamed for generating toxic forms of culture and ways of life. Once part of future imaginaries that were optimistic or even utopian, today there is a sense that things have turned out very differently. Anti-computing is widespread. This book seeks to understand its cultural and material logics, its forms, and its operations. Anti-Computing critically investigates forgotten histories of dissent - moments when the imposition of computational technologies, logics, techniques, imaginaries, utopias have been questioned, disputed, or refused. It asks why dissent is forgotten and how - under what circumstances - it revives. Constituting an engagement with media archaeology/medium theory and working through a series of case studies, this book is compelling reading for scholars in digital media, literary, cultural history, digital humanities and associated fields at all levels.